Candida glabrata infection of a pancreatic pseudocyst in a COVID-19 patient: A case report and review of the literature - Khan, Mohammad Aasim; Almas, Talal; Ullah, Muneeb; Alkhattab, Maha; Shaikh, Fathema; Shaikh, Sufyan; Bagwe, Isha; Antony, Meetty; Khedro, Tarek; Nagarajan, Vikneswaran Raj; Ramjohn, Joshua; Alsufyani, Reema; et al. (Lippincott Williams & Wilkins, 2022)
Introduction Pancreatic pseudocysts remain a feared complication of acute or chronic pancreatitis and are often characterized by collections of fluids due to underlying damage to the pancreatic ducts, culminating in a walled-off region bereft of an epithelial layer but surrounded by granulation tissue. While fungal infections of pancreatic pseudocysts are rarely encountered, candida albicans remains the most frequently implicated organism.